Are the Russian Banks Threatened with Removal from SWIFT? A Multiple Case Study on Interbank Financial Messaging Systems (International Journal of Scientific Research and Management (IJSRM), 2022)
When Russia invaded Ukraine in February 2022, the United States, European Union, and their allies removed the Russian banks from the main interbank payment system worldwide, SWIFT (Society for Worldwide Interbank Financial Telecommunication), which is a secure messaging system that makes cross-border payments possible, vital for the international trade. However, it is not the first time that Russian banks are threatened with disconnection from Swift by the US government. In response, the Central Bank of Russia developed in 2014 the SPFS (System for Transfer of Financial Messages, our translation). In addition, the Chinese government created in 2015 an equivalent system named Cross-Border Interbank Payment System (CIPS). In this article, we examined SWIFT and alternatives, such as the Russian SPFS, the Chinese CIPS, and the Indian SFMS. Key findings pointed out crucial differences between the financial messaging systems, their objectives, and the expansion of operations overseas. Finally, discussion and implications to the global economy compile this work.